The Use Of Active Knowledge Sharing Strategies In Critical Thinking Ability In The 21st Century Generation - Vini Wela Septiana; Jamaris; Sufyarma Marsidin (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study aims to see the students' Critical Thinking Ability. Through the use of Active Sharing Knowledge Strategies to prepare materials for the 21st-century generation of critical reading in Indonesian Mi/SD language learning courses. This research begins with a literature study carried out in May-June of the 2021/2022 academic year, at the Muhammadiyah University of West Sumatra, Faculty of Islamic Religion Prodi Pendidikan Guru Madrasah Ibtidaiyah. The sample of this study consisted of one class, the determination of the sample class using the purposive sampling technique. This type of research is survey research with a qualitative approach. The method used in this research is an experiment, which aims to determine a symptom or effect that arises, as a result of something certain treatment. The data obtained were analyzed using quantitative data analysis techniques. The data obtained is the students' critical thinking ability. critical thinking skills assessment is carried out according to six critical thinking indicators, namely: 1) Focus (focus), 2) Arguments (reasons), 3) Conclusion (inference), 4) Situation, 5) Clarity (Clarity), 6) Follow-up Review (Overviews). The results show that from the 17 critical thinking questions tested, different presentations were obtained. 45% of the students' answers were in the very good category and 55% in the good category. This proves that students' thinking on critical reading material.